The Intelligence Community Debate over Intuition versus Structured Technique:: Implications for Improving Intelligence Warning and Analysis - Khalsa, Sundri (Journal of Conflict Studies, 2009)
ABSTRACT A long-standing debate divides many analysts in the intelligence community over whether structured techniques work on complex problems, such as intelligence analysis. The non-structured approach has become the norm in the intelligence community. This article describes both sides of the debate and argues that using systematic processes is better than intuition alone. Most importantly, this article asserts that the intelligence community should acknowledge the results of the debate and take a major step by committing to a uniform set of standards (indicators and methodology) that combine intuition and structured technique for the standing intelligence warning topics. Recommendations for implementation are described in a proposed methodology model that identifies a uniform set of standards to improve intelligence warning.